2009
DOI: 10.1007/s11250-009-9487-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic parameters for faecal egg count of Haemonchus contortus infection and relationship with growth traits in Avikalin sheep

Abstract: Genetic parameters for faecal egg count were estimated in naturally challenged Avikalin sheep developed and maintained at Central Sheep & Wool Research Institute, Avikanagar, India, over a period of 4 years (2004-2007). The data on faecal egg count for 433 animals descended from 41 sires, and 151 dams were used for the study. Genetic analyses were carried out using restricted maximum likelihood, fitting an animal model and ignoring or including maternal genetic or permanent environmental effects. Direct herita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
4
4
0
Order By: Relevance
“…The estimates of direct heritabilities (0.11 to 0.16) of FEC in the present study were similar to the findings of Woolaston and others (1992) in adult meat‐type goats (0.08) and Baker and others (2001) in Galla and small East African goats (0.12). Similarly, the present estimates are in the same range as those obtained by Greeff and Karlsson (1998), Gauly and Erhardt (2001) and Prince and others (2010) in sheep. However, higher estimates (Rohrer and others 1991, Mandonnet and others 2001) and lower estimates (Morris and others 1997) than the present findings have been observed in other goat breeds.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The estimates of direct heritabilities (0.11 to 0.16) of FEC in the present study were similar to the findings of Woolaston and others (1992) in adult meat‐type goats (0.08) and Baker and others (2001) in Galla and small East African goats (0.12). Similarly, the present estimates are in the same range as those obtained by Greeff and Karlsson (1998), Gauly and Erhardt (2001) and Prince and others (2010) in sheep. However, higher estimates (Rohrer and others 1991, Mandonnet and others 2001) and lower estimates (Morris and others 1997) than the present findings have been observed in other goat breeds.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the present estimates are in the same range as those obtained by Greeff and Karlsson (1998), Gauly and Erhardt (2001) and Prince and others (2010) in sheep. However, higher estimates (Rohrer and others 1991, Mandonnet and others 2001) and lower estimates (Morris and others 1997) than the present findings have been observed in other goat breeds.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, within-breed genetic variation has also been demonstrated in diverse sheep populations including Merino [11], Romney [12], Scottish Blackface [13], feral Soay sheep [14], etc. Estimation of genetic parameters revealed low to moderate heritability in different sheep populations (h 2  = 0.149, Avikalin sheep [15] to h 2  = 0.41, Armidale sheep [16]). …”
Section: Introductionmentioning
confidence: 99%
“…but not upto such extend when these drugs are 100 % effective. Prince et al (2010) reported that there is a direct effect of faecal egg count on growth characteristics i.e. whenever faecal egg count is high, average daily weight gain declines.…”
Section: Resultsmentioning
confidence: 99%